Stochastic and Conditional Regulation of Nematode Mouth-Form Dimorphisms - Susoy, Vladislav; Sommer, Ralf J. (Frontiers in Ecology and Evolution, 2016)
Integrative research at the interphase between ecology, developmental, and evolutionary biology increasingly highlights the importance of phenotypic plasticity, the property of a single genotype to produce different phenotypes depending on environmental conditions. Plasticity occurs in multiple forms at the morphological, physiological, and behavioral levels. It can be reversible or irreversible, continuous or discrete, the latter also known as “polyphenism”. While plasticity has long been discussed as a concept of both, ecological and evolutionary significance, only recent experimental studies have begun providing insights into the associated molecular mechanisms. One promising system for genetic and molecular analyses of phenotypic plasticity is a feeding polyphenism in the nematode model organism Pristionchus pacificus. In this species, genetically identical nematodes can express two alternative mouth-forms, which are advantageous under different environmental conditions. Although the expression of these mouth-forms can be influenced by environment, even under fixed environmental conditions, genetically identical individuals of P. pacificus form both morphs. Thus, in addition to conditional regulation, mouth dimorphism in P. pacificus is regulated stochastically. Here, we discuss the importance of the stochastic regulation of the switch between alternative phenotypes and show that this characteristic provides a unique advantage for genetic, molecular, and experimental analyses. We then relate this stochasticity in mouth-form regulation to a similar phenomenon seen in bacteria, bistability, and finally discuss stochasticity as a bet-hedging mechanism for living in unpredictable environments.